Inorganic chemistry = - Wiberg, Egon (Academic Press, 2001)
Inorganic Chemistry easily surpasses its competitors in sheer volume and depth of information. Readers are presented with summaries that ease exam preparation, an extensive index, numerous references for further study, six invaluable appendixes, and over 150 tables that provide important data on elements at a quick glance